Kohustus kannatada, et näha ja mõista. Ene Mihkelsoni ja Ingeborg Bachmanni kirjanikunägemus. The Writer’s Duty to Suffer in Order to See and Understand: The Literary Vision of Ene Mihkelson and Ingeborg Bachmann - Aija Sakova (Methis: Studia Humaniora Estonica, 2010)
In an interview from 1971 the Austrian poet and author Ingeborg Bachmann (b 1923) said that there are phenomena that science and scientific language cannot explain. According to her these are the phenomena that belong to the realm of writers and literature. In the same year Ene Mihkelson (b 1946), who had not yet published a single book of poetry or a novel because of censorship, pondered on the role of the author within society: “The author digs under the surface and the author’s responsibility to society lies in his/her persistence, in his/her duty to suffer, to endure stress, which the people in the midst of their busy, daily lives are unable to fully grasp.” Responsibility to society and the duty to suffer and explore the deepest layers below the surface are common to both Mihkelson and Bachmann. Both writers were born and grew up in the shadow of war, violence and totalitarianism. Mihkelson was brought up in a guerrilla family in Soviet Estonia; Bachmann spent her childhood years growing up in the Nationalist-Socialist Austria and in her youth she witnessed the Second World War and its catastrophic consequences. So both of them understand that as writers they cannot overlook the events that they had, either directly or indirectly, witnessed. In an interview from 2009 Mihkelson said that the fact that she remained alive while many did not, that she was not deported to Siberia although it could have happened, has obligated her to write and reflect on what had happened. No consensus has been reached in Europe to condemn Communism as a crime against humanity, but for Estonians Communism and the 50 years of Soviet regime signify a lengthy experience of a totalitarian regime and, in spite of a possible opposition from German-speaking cultures, Communism very often equals Nazism in Estonia. According to Mihkelson, in order to understand and reflect this experience it is not sufficient to rely only on the archives, biographies and books of history or interviews with survivors. She agrees that they are necessary as preparatory work but argues that only by writing about the experience is it possible to understand it. Imagining and making it real (in German darstellen and wahr machen) are keywords that are essential for understanding the works of Mihkelson and Bachmann, and this is possible through a very personal relationship with language, and through the material that they write about. So we can say that the work of both authors is characterized by a rejection of commonplace plots and clear-cut characters in favour of certain intenseness, as well as an extremely subjective or personal style of writing that includes both the person of the author as well as the author’s private experience. What this very personal approach means for the poetics of the text and what exactly is expressed through it, I have tried to show in an article on the prologue to Bachmann’s novel Malina (1971), which is a recollection of the first person narrator’s early childhood. I have also analyzed Mihkelson’s novel Ahasveeruse uni (The Sleep of Ahasuerus, 2001) in which the first person narrator reveals her experience of fear, which she had first removed from her recollections and which she remembers later when she stumbles upon a rat in her country house. The first-person narrator says at the beginning of the novel Malina that she must and will tell a story, as there is nothing that disturbs her in her memories, but then adds quickly that she is actually very far from the moment where the suppressed memories do not disturb her. So we can understand from the prologue that the novel that is being introduced is, in a way, a recollection of the memories and moments where pain and violence and the man-woman relationship gone awry take root. The first real experience of pain which, in a way, is not integrated and thus becomes a suppressed memory, is a recollection about a boy, a few years older than she was at the time, who slapped her in the face when she was six years old. Bachmann describes this extremely humiliating situation which was not only connected with pain, but also with fear, and shows very laconically but also skilfully how horrible this experience was for the firstperson narrator and what extensive consequences it had. She also points out that at the moment the girl did not weep the tears that were necessary, and did not integrate the humiliating experience that she had had to go through, which then becomes her first suppressed memory and is localized as the beginning for subsequent disappointments in human relationships. The following “intellectual autobiography”, as Bachmann calls it, contains, among other things, a whole array of horrible stories, which the first-person narrator recalls and which have influenced her relationships with men. According to Jaak Tomberg, this kind of writing represents “the reconciliatory function of literature” (cf Tomberg 2009). In other words, the recollection of a slap in the face might be a failed opportunity in the past, as the first-person narrator did not do anything, did not strike back or shed any tears. In this way Bachmann’s novel can be seen in terms of the weak messianistic power of literature, according to Tomberg, who resorts to Walter Benjamin, as the failed opportunities in the past are reconciled with the present by recollecting or writing about them. The article shows how in their fiction Mihkelson and Bachmann seek – through writing – to redeem the failed opportunities and the pain and violence experienced in the past. By deeply personal and painful form of insight Mihkelson and Bachmann oppose the totalitarian patterns of behaviour and the influences of totalitarian regimes, making them visible so that the readers would see and understand the things that might not be visible at first glance. At the same time they search for the means of expression that would enable them to put into words something that seems impossible to talk about.